Social psychology - Myers, David G. (McGraw-Hill, 2013)
Social psychology is about people. This text never loses sight of that idear, forcusing on a humanly significiant issues and opening each chapter with a vignette that relates the theme of the chapter to the human experience. However, the cutting edge of social psychological research is at the forefront as well.....